Sistem Absensi Siswa Berbasis Website Dengan Notifikasi Whatsapp Menggunakan Metode Rapid Application Development (RAD) - Deswita, Tatia; Butsianto, Sufajar; Riandani, Andini Putri (Jurnal Teknologi Komputer dan Informasi, 2026)
The student attendance system is still largely conducted manually, resulting in problems such as recording errors, delays in data recap, and lack of information to parents. This study aims to develop a website-based student attendance system integrated with WhatsApp notifications using the Rapid Application Development (RAD) method. The RAD method is used to accelerate the development process through the stages of planning, designing, building, and implementation. The system is built using PHP, Laravel, MySQL, and WhatsApp Gateway as a notification medium. The results of the study indicate that the system can improve the efficiency and accuracy of attendance recording and send notifications to parents in real-time. System testing shows that all features work well, making the system suitable for use.